Implementing Admission Screening for Candida auris. (October 2020) - Rasmusson, Jenna; Wengenack, Nancy; Sampathkumar, Priya
Abstract : Background: Candida auris is a globally emerging, multidrug-resistant fungal pathogen that causes serious, difficult-to-treat infections in hospitalized patients. C. auris cases in the United States have been linked to receipt of healthcare overseas. Outbreaks have also occurred in New York City, New Jersey, Chicago, and most recently in California. We provide care to patients from all 50 states and 138 countries; therefore, we are at risk for encountering C. auris in our facility. Setting: An academic, tertiary-care center with 1, 297 licensed beds and >62, 000 admissions each year. Methods: Infection prevention and control (IPAC) initiated a C. auris screening program in August 2019 in partnership with the State Health Department. A case-finding tool was created to identify adult patients admitted in the previous 24 hours from countries and areas of the United States (Chicago, New Jersey, and New York metropolitan areas) with known C. auris transmission based on the zip code of their primary address. IPAC sends an electronic communication via the electronic medical record (EMR) alerting the patient care team that the patient meets criteria for screening along with information on C. auris and links to a tool kit with additional resources to help answer questions. After obtaining verbal consent, the patient's primary nurse collects a composite axilla–groin skin swab using a nylon-flocked swab (BD ESwab collection and transport system; Becton Dickinson, Sparks, MD). The sample is sent to the State Health Department laboratory for testing by polymerase chain reaction (PCR). Results are communicated back to IPAC and then scanned into the patient's EMR. Results: From August 2019 to November 2019, 157 patients were identified for C. auris screening using the case-finding tool. Testing was performed on 95 patients; all tests were negative. The primary reasons for testing not to be performed on eligible patients were inability to obtain verbal consent and patient dismissal before sample could be obtained. The need for a special swab that is not routinely stocked on patient care units has been a limitation to timely specimen collection. Conclusions: The EMR can be leveraged for early identification and screening of patients at risk of C. auris colonization. Case finding tools can be effectively replicated and modified to respond to emerging infections and changing surveillance guidelines. Funding: None Disclosures: None